Novel Directional Nanoantennas for Single-Emitter Sources and Wireless Nano-Links - Maciej Klemm (International Journal of Optics)
Optical nanoantennas are emerging as one of the key components in the future nanophotonic and plasmonic circuits. The first optical nanoantennas were in a form of simple spherical nanoparticles. Recently more complex Yagi-Uda nanoantenna structures were demonstrated. These nanoantennas enhance radiation of single emitters and provide well-defined directional radiation. In this contribution, we present the novel design of the directional nanoantenna, which is excited from the propagating mode of the plasmonic waveguide. The nanoantenna design is based on the travelling wave principle, well known at RF/microwave frequencies. By properly designing the propagating parts of the nanoantenna, a very efficient coupling to free space wave impedance can be achieved. Furthermore, the control over the radiation direction and beam width is relatively easy with this nanoantenna. Compared to the previously published Yagi-Uda designs, the new nanoantenna presented in this work has directivity three times higher.